Feasibility of school-based computer-assisted robotic gaming technology for upper limb rehabilitation of children with cerebral palsy. - Preston, Nick; Weightman, Andrew; Gallagher, Justin; Holt, Raymond; Clarke, Michael; Mon-Williams, Mark; Levesley, Martin; Bhakta, Bipinchandra (Disability & Rehabilitation: Assistive Technology, 2016)
Introduction: We investigated the feasibility of using computer-assisted arm rehabilitation (CAAR) computer games in schools. Outcomes were children's preference for single player or dual player mode, and changes in arm activity and kinematics.Method: Nine boys and two girls with cerebral palsy (6–12 years, mean 9 years) played assistive technology computer games in single-user mode or with school friends in an AB–BA design. Preference was determined by recording the time spent playing each mode and by qualitative feedback. We used the ABILHAND-kids and Canadian Occupational Performance Measure to evaluate activity limitation, and a portable laptop-based device to capture arm kinematics.Results: No difference was recorded between single-user and dual-user modes (median daily use 9.27 versus 11.2 min,p = 0.214). Children reported dual-user mode was preferable. There were no changes in activity limitation (ABILHAND-kids,p = 0.424; COPM,p = 0.484) but we found significant improvements in hand speed (p = 0.028), smoothness (p = 0.005) and accuracy (p = 0.007).Conclusion: School timetables prohibit extensive use of rehabilitation technology but there is potential for its short-term use to supplement a rehabilitation program. The restricted access to the rehabilitation games was sufficient to improve arm kinematics but not arm activity.Implications for RehabilitationSchool premises and teaching staff present no obstacles to the installation of rehabilitation gaming technology.Twelve minutes per day is the average amount of time that the school time table permits children to use rehabilitation gaming equipment (without disruption to academic attendance).The use of rehabilitation gaming technology for an average of 12 minutes daily does not appear to benefit children's functional performance, but there are improvements in the kinematics of children's upper limb.